Huckleberry Hill - Beckstrand, Jennifer (New York, NY : Zebra Books/Kensington Publishing Corp., 2014)
In this first book in a series set in Huckleberry Hill, Wisconsin, two octogenarian Amish folks try their hands at matchmaking, pairing the quiet and gentle Moses Zimmerman with the tall and sturdy Lia Shetler.
"Zebra inspirational romance"--Spine.
Includes an excerpt from Huckleberry summer (p [345]-347).
Keywords: Amish -- Fiction; Christian fiction; Wisconsin -- Fiction; Love stories